Professor V.G. Shlopov – an outstanding representative of domestic pathological anatomy (to the 80th birthday) - D.D. Zerbino; Yu.B. Chaikovskyi; V.I. Chernii; T.V. Sviatenko; L.I. Volos; I.V. Svystunov; T.Ye. Mykhailychenko (Medičnì Perspektivi)
Professor V.G. Shlopov – an outstanding representative of domestic pathological anatomy (to the 80th birthday)